2015
DOI: 10.1177/1350650115588568
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of structural and tribological properties of electroless Ni–B coated pure titanium

Abstract: In the present study, the surface of commercial pure (Grade 2) titanium was coated with electroless Ni-B and, then, it was subjected to heat treatment for an hour at 400 C. The surface morphology, microstructure and phase identification were analysed by X-ray diffraction and scanning electron microscope. Wear behaviour characterisation was carried out using a ball-on-disc tribometer. The results of the analyses showed that the electroless Ni-B coating had a significantly amorphous structure in the as-deposited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 31 publications
(34 reference statements)
5
15
0
1
Order By: Relevance
“…This could be an indication of higher thermal stability of the deposits [29,39]. High microhardness of heat treated Ni-B and its ternary variants are in accordance with the literature [23][24][25][26][27][28][29].…”
Section: Microhardness Of Nickel Boron and Its Variantssupporting
confidence: 89%
See 3 more Smart Citations
“…This could be an indication of higher thermal stability of the deposits [29,39]. High microhardness of heat treated Ni-B and its ternary variants are in accordance with the literature [23][24][25][26][27][28][29].…”
Section: Microhardness Of Nickel Boron and Its Variantssupporting
confidence: 89%
“…Therefore, for thin coatings, it is always suitable to address nano-hardness instead of micro-hardness, keeping in mind the thickness of the films. While EN coatings have been widely characterized by the micro-indentation technique in other research works [23,25], the microhardness results reported in Table 5 are in line with them. Furthermore, as the present work considers a similar group of coatings and their comparative study with consistent indentation depth for all the three variants, the results are comparable within the coating groups.…”
Section: Microhardness Of Nickel Boron and Its Variantssupporting
confidence: 76%
See 2 more Smart Citations
“…The columnar growth of Ni-B coatings reduces their actual area of contact, and acts as a pocket for retaining lubricants [4]. The mechanical and wear properties are further enhanced during heat treatment, due to the precipitation of hard boride phases [5]. Thermochemical treatment/nitriding and vacuum heat treatment have a positive effect on the coating properties [6][7][8].…”
Section: Introductionmentioning
confidence: 99%